Adverse reproductive outcome induced by Parvovirus B19 and TORCH infections in women with high-risk pregnancy - Kishore, Janak; Misra, Richa; Paisal, Abhiruchi; Pradeep, Yashodhra (The Journal of Infection in Developing Countries, 2011)
Introduction: The frequency of fetopathogenic viruses and Toxoplasma gondii infections in the TORCH group (Toxoplasma gondii, rubella virus, cytomegalovirus (CMV), herpes simplex virus) together with Parvovirus B19 (B19) in pregnant women with bad obstetric history (BOH) and/or concurrent pregnancy complications was investigated. Methodology: Sixty women (20-35 years) with BOH and/or antecedent pregnancy complications were studied. Twenty-nine healthy pregnant women matched for age, parity and gestational age served as controls. Sera were analyzed for IgM antibodies for B19 and TORCH agents by ELISA. Cord blood and 33 placental tissues from six malformed newborns were tested for B19 DNA by PCR. Results: Out of 60 high-risk pregnant women, 47 (78%) had BOH while 23 (38.3%) had underlying complications including polyhydramnios (n=10), oligohydramnios (n=6) and intrauterine growth restriction (n=7). Adverse outcomes occurred in 36 (60%) high-risk cases. All 16 cases with polyhydramnios/oligohydramnios resulted in preterm stillbirths while the remaining 20 cases resulted in seven abortions, six newborns with congenital malformations, four full-term stillbirths and three cases of non-immune hydrops fetalis (NIHF). IgM positivity to T. gondii, rubella, cytomegalovirus, herpes simplex virus and B19 virus was 8.3%, 15%, 30%, 3.3% and 13.6% respectively. B19 infection caused NIHF in three cases and cardiac anomaly in one. All placental tissues and cord blood were negative for B19 DNA. None of the controls had IgM antibodies to any pathogen. Conclusions: Women with BOH and/or pregnancy complications had a high frequency of TORCH and parvovirus B19 infections causing fetal wastage, IUGR, NIHF and congenital malformations.